Corona virus affects fertility: A concern - Dharmendra Kumar; Rishabha Malviya; Pramod Kumar Sharma (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2020)
CORONAVIRUS is spherical or pleomorphic, single stranded, enveloped RNA and covered with club shaped glycoprotein. CORONAVIRUSES are four sub types such as alpha, beta, gamma and delta CORONAVIRUS. First case of CORONAVIRUS was notified as cold in 1960. According to the Canadian study 2001, approximately 500 patients were identified as Flu-like system. COVID-19 was first identified and isolated from pneumonia patent belongs to Wuhan, china [1].